2015
DOI: 10.1515/jpm-2014-0207
|View full text |Cite
|
Sign up to set email alerts
|

Can routine laboratory parameters predict adverse pregnancy outcomes in intrahepatic cholestasis of pregnancy?

Abstract: Our study suggests that increased MPV and total bilirubin levels are associated with preterm delivery, and increased postprandial total SBA levels are predictive for low APGAR in ICP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 8 publications
2
26
0
1
Order By: Relevance
“…Conversely, other studies have concluded that maternal clinical and laboratory features, including elevated TBA, do not appear to be significant predictors of fetal complications in gravidas with ICP . A study by Oztas et al suggested that there is no association between TBA levels and preterm delivery. Indeed, there are undefined conclusions in this relation between TBA quantitative category levels and perinatal outcomes, such as PTB, MSAF, asphyxia, and RDS.…”
Section: Introductionmentioning
confidence: 95%
“…Conversely, other studies have concluded that maternal clinical and laboratory features, including elevated TBA, do not appear to be significant predictors of fetal complications in gravidas with ICP . A study by Oztas et al suggested that there is no association between TBA levels and preterm delivery. Indeed, there are undefined conclusions in this relation between TBA quantitative category levels and perinatal outcomes, such as PTB, MSAF, asphyxia, and RDS.…”
Section: Introductionmentioning
confidence: 95%
“…Cui et al reported that total bile acid levels ≥ 40 μmol/L are considered to represent severe disease [12]. Although several studies have reported a positive correlation between elevated serum total bile acids and an increased risk of perinatal complications, there are also controversial results [14,15]. A study by Oztas et al stated that there is no relationship between serum total bile acid levels and preterm delivery [14].…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have reported a positive correlation between elevated serum total bile acids and an increased risk of perinatal complications, there are also controversial results [14,15]. A study by Oztas et al stated that there is no relationship between serum total bile acid levels and preterm delivery [14]. Madazlı et al also stated that there was no significant difference between the incidence of RDS, foetal distress and preterm delivery according to serum bile acid levels [10].…”
Section: Discussionmentioning
confidence: 99%
“…While pregnant, women can have jaundice, steatorrhea [10] and increased risk of preeclampsia [16]. Enhanced blood coagulation has been noted through increases in mean platelet volume [17] along with significant increases in factor VIII, von Willebrand factor and fibrinogen levels [18]. Much later in life, women who have had ICP are more prone to a variety of health complications.…”
Section: Risk Factors and Effects Of Icpmentioning
confidence: 99%
“…The neutrophil-to-lymphocyte ratio is significantly higher in women with ICP [17, 61]. In fact, as the severity of ICP increases based on levels of bile acids, there is an increase in the ratio of neutrophils-to-lymphocytes [61].…”
Section: Immunologymentioning
confidence: 99%